GlitzGlam makeup brush / Nur Insyirah Irdina Azizan … [et al.] - Azizan, Nur Insyirah Irdina; Ahmad Suhailee, Natasha; Rasali, Sarah Aisyah; Nazib, Nadia; Lugo, Stephanie Sungau; Husain, Nor Azmawati (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
GlitzGlam presents an innovative cosmetics brush range designed exclusively for people with disabilities with the goal of enhancing accessibility and inclusivity in daily beauty regimens. These cosmetic tools are made to make applying makeup easier, especially for those with special needs, encouraging self- confidence and independence. Ergonomic handles, magnetic attachments, textured grips, adjustable lengths, configurable brush sets, and braille labeling are just a few of the creative features that guarantee accessibility and convenience of use. For individuals with special needs, GlitzGlam's brush set—which combined functions for blusher, foundation, and eyeshadow brushes—is a vital tool that helps them look and feel more like professionals. GlitzGlam is transforming the beauty market by emphasizing inclusivity and accessibility. This is enabling everyone to express themselves creatively and confidently via cosmetics, thereby creating a more varied and equitable industry.